Analisis Faktor Perilaku Buang Air Besar Sembarangan (BABS) Di RW 15 Kelurahan Tangkerang Utara Wilayah Kerja Psekesmas Sapta Taruna Tahun 2022 - Frecilia Sandy; Winda Septiani; Zulmeriza Rasyid; Agus Alamsyah; Hoppy Dewanto (Jurnal Kesehatan Komunitas, 2023)
Open Defecatio is an activity that reflects a person's behavior, where a person is defecating carelessly anywhere such as rivers, fields, and shrubs. The purpose of this study was to determine the Analysis of Factors of Open Defecation Behavior in RW 15 North Tangkerang Village, the work area of the Sapta Taruna Health Center. This type of research is quantitative with a case-control design with a sample of 80 households with a ratio of 1: 3, namely 20 case samples and 60 control samples. Data were collected by interview and observation methods using questionnaire data collection tools. The method of sampling cases in total sampling and the method of sampling control by Propotional Random Sampling. The data will be processed with univariate and bivariate analysis to see the comparison using the chi-square test carried out computerized. From the results of the research on the relationship of knowledge in 20 cases, there are 11 household (55%) respondents knowledgeable. lowWhile 60, control there are 34 families (56,7%) knowledgeable high with (p-value 0,007). Obtained with the attitude respondents from 20 cases, there are 14 families (70 %) respondents who have the good. While 60, control there are 37 families (61,7%) having good behavior with obtained (p-value 0,007). In terms of the privy ownership of 20 cases, there are 13 families (65%) of respondents whose possession is privy. ineligibleWhile 60, control there are 31 households (51,7%) whose possession privy qualified with obtained (p-value 0,041). While the supply of clean water from 20 cases there are 11 households (55.0%) that have clean water availability ineligible. healthWhile 60, control there are 32 households (53,3%) that clean water supply qualified health (p-value 0,027). The role of health workers from 20 cases there are 15 families (75.0%) role that health workers. play no roleWhile 60, control there is 38 families (63,3%) role with the role of health workers who obtained (p-value 0,037), it means it can be concluded the knowledge, attitude, ownership of privy, of clean water supply and the role of health workers to the behavior defecate carelessly. This research is expected to give you an idea for the local community health center and urban village to minimize of risk of defecation in the community to not sustainable.